The Russian people and foreign policy : Russian elite and mass perspectives, 1993-2000 - Zimmerman, William, 1936- (Princeton University Press, 2002)
Since the fall of communism, public opinion in Russia, including that of a now more diverse elite, has become a substantial factor in that country's policymaking process. What this opinion might be and how it responds to American actions is the subject of this study. William Zimmerman offers important and sometimes disturbing insight into the thinking of citizens in America's former Cold War adversary about such matters as NATO expansion. Drawing on nearly a decade of unprecedented surveys he conducted with a wide spectrum of the Russian public, he gauges the impact of Russia's opening on its.